Wing plasticity and associated gene expression varies across the pea aphid biotype complex. (1st May 2021) - Parker, Benjamin J.; Driscoll, Rose M. H.; Grantham, Mary E.; Hrcek, Jan; Brisson, Jennifer A.
Abstract: Developmental phenotypic plasticity is a widespread phenomenon that allows organisms to produce different adult phenotypes in response to different environments. Investigating the molecular mechanisms underlying plasticity has the potential to reveal the precise changes that lead to the evolution of plasticity as a phenotype. Here, we study wing plasticity in multiple host‐plant adapted populations of pea aphids as a model for understanding adaptation to different environments within a single species. We describe the wing plasticity response of different "biotypes" to a crowded environment and find differences within as well as among biotypes. We then use transcriptome profiling to compare a highly plastic pea aphid genotype to one that shows no plasticity and find that the latter exhibits no gene expression differences between environments. We conclude that the loss of plasticity has been accompanied by a loss of differential gene expression and therefore that genetic assimilation has occurred. Our gene expression results generalize previous studies that have shown a correlation between plasticity in morphology and gene expression.